2018
DOI: 10.1097/fpc.0000000000000316
|View full text |Cite
|
Sign up to set email alerts
|

Race/ethnicity difference in the pharmacogenetics of bilirubin-related atazanavir discontinuation

Abstract: BackgroundAtazanavir causes plasma indirect bilirubin to increase. We evaluated associations between Gilbert’s polymorphism and bilirubin-related atazanavir discontinuation stratified by race/ethnicity.Patients and methodsPatients had initiated atazanavir/ritonavir-containing regimens at an HIV primary care clinic in the southeastern USA, and had at least 12 months of follow-up data. Metabolizer group was defined by UGT1A1 rs887829 C→T. Genome-wide genotype data were used to adjust for genetic ancestry in comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…Since allele frequencies vary across ethnicities, we would be hesitant to extrapolate the reported results to ethnicities not included in the underlying publications. While for TMPT ( McLeod et al, 1999 ) allele frequencies are fairly constant across ethnicities, the frequency of actionable phenotypes are higher for UGT1A1 in Blacks and Hispanics ( Leger et al, 2018 ), CYP2C19 in Asians ( Zhou et al, 2017 ) and DPYD in Africans ( Mattison et al, 2006 ) and therefore the current analysis underestimates cost-effectiveness in these ethnicities. Thirdly, the current model was constructed for the Netherlands.…”
Section: Discussionmentioning
confidence: 76%
“…Since allele frequencies vary across ethnicities, we would be hesitant to extrapolate the reported results to ethnicities not included in the underlying publications. While for TMPT ( McLeod et al, 1999 ) allele frequencies are fairly constant across ethnicities, the frequency of actionable phenotypes are higher for UGT1A1 in Blacks and Hispanics ( Leger et al, 2018 ), CYP2C19 in Asians ( Zhou et al, 2017 ) and DPYD in Africans ( Mattison et al, 2006 ) and therefore the current analysis underestimates cost-effectiveness in these ethnicities. Thirdly, the current model was constructed for the Netherlands.…”
Section: Discussionmentioning
confidence: 76%
“…This syndrome is associated with the UGT1A1*28 allele, defi ned by the presence of seven repetitions of the dinucleotide TA (TA7) in the gene's promoting region that codes the enzyme, which translates into reduced enzyme activity and asymptomatic hyperbilirubinemia. [52] Another study confi rmed the association between this allele and risk of hyperbilirubinemia; 67% of the individuals homozygous for the UGT1A1*28 allele who received ATV or IDV had at least two episodes of hyperbilirubinemia, compared with 7% in the group not treated with either of these drugs. The UGT1A1*28 allele is the cause of Gilbert syndrome.…”
Section: Review Articlementioning
confidence: 98%
“…However, when stratified by race, hazard ratio [HR] for discontinuation in White subjects (N = 152) was 14.4 (95% CI: 2.6–78.7; P = 0.002), but 0.8 (95% CI: 0.05–12.7; P = 0.87) for Black subjects (N = 153). The authors speculate that if jaundice as a result of hyperbilirubinemia is less obvious in individuals with darker skin, it may explain the decrease in bilirubin-associated discontinuation in Black subjects as compared to White subjects [61]. An earlier genomewide association study (GWAS) of 475 patients administered ATV/r as part of the AIDS Clinical Trial Protocol Group A2502 previously found that the T allele at rs887829 in the promoter region of UGT1A1 (c.-364 C>T) was associated with increased peak bilirubin concentrations ( P =6.4×10 –12 ) [62].…”
Section: Pharmacogenomics Of Atv/rmentioning
confidence: 99%